IMPLEMENTATION OF THE ADIWIYATA-BASED CURRICULUM IN ENGLISH LEARNING ACTIVITY AT MTsN 1 SIDOARJO - Nur Alilah; Siti Chodijah; Nabila Ainisshifa; Affan Heryana Santana; Effi Susanti; Fitriah Fitriah (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
This research is focused on the  implementation of  the Adiwiyata-based curriculum in English learning at MTsN 1 Sidoarjo. The researcher applies a  qualitative descriptive method which aims to determine the implementation of the Adiwiyata school program and its implementation in learning English. Data collection technique that is used in this study is qualitative data which are gained from observation,interview,and field note. Furthermore, the qualitative data are analyzed by: assembling the data, coding the data, comparing the data, building interpretations, and reporting the outcomes. The result of the research shows that (a) the Adiwiyata-based curriculum adds or inserts indicators that are integrated with the environment; (b) The procedure for developing adiwiyata-based curriculum is the same as in the general curriculum; (c) Implementation of the adiwiyata-based curriculum, starting from the preparation of lesson plans to learning activities and other activities related to the environment; (d) The purpose of implementing the Adiwiyata-based curriculum at MTsN 1 Sidoarjo. Hence, the findings reveal that  implementation of the Adiwiyata-based curriculum in English learning at MTsN 1 Sidoarjo was successfully viewed from a certain perspective.